Radiation grafted poly(ethylene terephthalate)-graft-polystyrene pervaporation membranes for organic/organic separation - Khayet, Mohamed; Nasef, Mohamed Mahmoud; Mengual, Juan I. (Elsevier B.V., 2005)

(untitled)
Poly(ethylene terephthalate)-graft-polystyrene (PET-g-PST) membranes have been prepared using radiation-induced graft copolymerisation of styrene onto poly(ethylene terephthalate) (PET) films by simultaneous irradiation from Î³-radiation. The chemical structure, thermal characteristics, crystallinity and thermal stability of the so obtained membranes were investigated by means of Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and thermal gravimetric analysis. The surface properties of all membranes were investigated by contact angle measurements. The total and the components of the surface free energy together with the works of adhesion and the solubility parameters of the membranes were determined. Wetting and surface properties were found to vary systematically depending on the degree of grafting. The swelling experiments and pervaporation separation of toluene/methanol mixtures over the entire range of concentration were investigated using both the un-grafted PET and the grafted PET-g-PST membranes. The obtained results have been discussed in terms of the solubility and the diffusivity of each component in the membranes and as function of the morphological characteristics of the membranes. The effect of the degree of grafting on the pervaporation performance of the membranes was also established. Flory-Huggins theory was applied to evaluate the binary interaction parameters between each membrane and the penetrants. It was found that PET-g-PST membranes exhibited better toluene selectivity than the un-grafted PET membrane while the permeation fluxes of the grafted membranes were lower. Grafted PET-g-PST membranes with degrees of grafting up to 35% were found to be better than the un-grafted PET for pervaporation of toluene/methanol system.